2007
DOI: 10.1177/1049731507313981
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of Reflective Counseling Group Supervision for Military Counselors in Taiwan

Abstract: The purpose of this study is to examine the effects of reflective counseling group supervision (RCGS) for military counselors. A convenience sampling method is adopted. Twenty-two military counselors participate in this study. Both qualitative and quantitative research methods are used for collecting and analyzing data. The results support our hypothesis that participants who received the RCGS would show a significant increase in their counseling competences. Four primary categories related to supervisory styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Supervision also has been linked to significantly enhanced clinical competency assessed via clinician self-report. For example, Der Pan, Deng, and Tsai (2008) found that participation in group supervision was linked to military counselors' (N ¼ 22) improvement on all scales of the Counseling Competence Inventory.…”
Section: Quantitative Non-controlled Studiesmentioning
confidence: 98%
“…Supervision also has been linked to significantly enhanced clinical competency assessed via clinician self-report. For example, Der Pan, Deng, and Tsai (2008) found that participation in group supervision was linked to military counselors' (N ¼ 22) improvement on all scales of the Counseling Competence Inventory.…”
Section: Quantitative Non-controlled Studiesmentioning
confidence: 98%
“…Recognition of the parent's feelings by the IMH‐HV therapist may allow the parent to feel less lonely and, similarly, may help the parent respond to the infant's need for attention and affection. In the absence of supervision that invites attention to emotion and to the experiences of the IMH‐HV therapist while with the infant and family, there is a heightened risk that the therapist will fail to recognize or respond to the emotional complexity and ambiguity of the clinical work (Jen Der Pan, Deng, & Tsai ). As noted in Shea's article in this issue, the trust in and use of the supervisory relationship is also associated with decreases in job burnout and increases in work satisfaction (Shea, ).…”
Section: Reflective Supervisionmentioning
confidence: 99%